A review of aspects of additive engineering in perovskite solar cells. Issue 1 (9th December 2019) - Mahapatra, Apurba; Prochowicz, Daniel; Tavakoli, Mohammad Mahdi; Trivedi, Suverna; Kumar, Pawan; Yadav, Pankaj
Abstract : Solar energy is a clean source of energy that can help fulfill the increasing global energy demand. Abstract : Solar energy is a clean source of energy that can help fulfill the increasing global energy demand. Among light harvesting devices, perovskite solar cells (PSCs) have been a focus of interest among next-generation photovoltaic (PV) technologies due to their incredible conversion efficiency (certified PCE of 25.2%) along with their lower cost and ease of fabrication. However, the presence of many transport barriers and defect trap states at the interfaces and grain boundaries has negative effects on PSCs; it decreases their efficiency and stability and increases the hysteresis effect. Further controlling the morphology, grain boundary, grain size, charge recombination and density of defect states in the perovskite layer is necessary to enhance its photovoltaic performance and stability. In this review, we summarize the intensive research efforts in aspects of additive engineering in PSCs, including physical and chemical passivation, and the use of a wide variety of organic and inorganic additives to address these issues. Here, we mainly focus on passivation techniques in the perovskite active layer and their effects on the PV performance and stability of PSCs; the grain boundaries and surface defects in the perovskite layer play major roles in the recombination, carrier lifetime and charge transfer of PSCs.